Satisfacción del visitante en el complejo turístico Camino al Sol del cantón Montalvo - Chimborazo Agualongo, Digna Johanna (2018)
The present research work was developed in the Camino al Sol Tourist Complex, which is located at km5 via Montalvo-Balsapamba, therefore, it is on the left margins of Pisagua Alto. It is a pleasant place where you can appreciate a great variety of flora and fauna and a lot of vegetation to its surroundings, in the place before we have identified the main problem as it is the unsatisfaction of the visitors this is because it does not have a good infrastructure, the inadequate tourism services offered by the site, few recreational areas for children this has led to the customers do not feel satisfied instead. The purpose of this project is to analyze the level of satisfaction of the visitor to improve the demand of tourists in the complex turístico Camino al Sol del Cantón Montalvo, on the other hand the categories of analysis of the independent and dependent varibles were analyzed with criteria of national authors and foreigners, in turn, a current diagnosis was made of the place, to improve the case study. For the development of the research a scientific methodology is used, different information collection techniques are applied that facilitate the collection of significant data, through surveys carried out in the tourist complex. Finally, a plan was designed to strengthen tourism services to meet the needs of the client.